KECAKAPAN KEPEMIMPINAN ISLAM DI ABAD 21 SESUAI AL-QURAN DAN SUNNAH - Ritman Hendra; Teti Rosminda; Leni Suryanti; Irma Aldiani (STAI Ma'had Aly Al-Hikam Malang, 2022)
The term leadership in Islam has four words, namely caliph, imam, guardian, and ulul amri. From that word, meanings will be found that will provide an understanding that a leader is a must for every human civilization. With changing times and the advancement of science, an Islamic leadership must be able to hone its abilities according to the development of the times it faces. The 21st century makes a leader have multiple characters that are in line with advances in science and technology, but that progress does not change the foundation of his footing, namely the Koran and Sunnah. Times may change, but Islamic leadership skills must be imprinted in him, namely correct knowledge, safe aqidah and fixed faith, three skills as Islamic leaders in the 21st century must be guarded and maintained.